The Effect of Wordwall-Based Interactive Learning Media and Learning Motivation on High School Students’ Informatics Learning Outcomes - Sri Sa'adah Mardiah; Jasrial (ISEJ : Indonesian Science Education Journal, 2026)
The rapid development of digital technology requires innovative learning approaches that improve student engagement and learning outcomes, particularly in informatics education. However, Classroom instruction is still frequently dominated by conventional methods that limit student participation and reduce conceptual understanding. This study aimed to analyse the effect of WordWall-based interactive learning media and learning motivation on senior high school students’ informatics learning outcomes. This study employed a quantitative, quasi-experimental design with a 2×2 factorial structure. The research involved 60 tenth-grade students at SMAN 1 Siberut Utara selected through purposive sampling. Students were divided into an experimental class using WordWall and a control class using conventional learning media. Data were collected through learning outcome tests and motivation questionnaires, and analysed using descriptive statistics and a Two-Way ANOVA. The findings showed that students taught using WordWall achieved higher learning outcomes than those taught conventionally. The highest posttest mean score was obtained by students with high learning motivation in the WordWall group (91.42), while the lowest score was found in students with low motivation in the conventional class (50.81). Statistical analysis demonstrated that learning media significantly affected learning outcomes (F = 38.32 > 4.013), learning motivation significantly affected learning outcomes (F = 108.84 > 4.013), and there was a significant interaction between WordWall and learning motivation on students’ learning outcomes (F = 5.58 > 4.013). The study concludes that WordWall-based interactive learning effectively improves informatics learning outcomes and creates a more engaging and meaningful learning environment aligned with 21st-century educational demands.